2010
DOI: 10.1111/j.1600-0404.2010.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of intravenous lacosamide in refractory nonconvulsive status epilepticus

Abstract: Koubeissi MZ, Mayor CL, Estephan B, Rashid S, Azar NJ. Efficacy and safety of intravenous lacosamide in refractory nonconvulsive status epilepticus.
Acta Neurol Scand: 2011: 123: 142–146.
© 2010 John Wiley & Sons A/S. Background –  Lacosamide (LCM) is a novel antiepileptic drug (AED) recently approved as an adjunctive therapy in the treatment of partial seizures in adults. LCM is available in oral and intravenous formulations, has linear pharmacokinetics and a unique mechanism of action. The aim of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 12 publications
0
41
0
4
Order By: Relevance
“…Other adverse events reported were angioedema, allergic skin reactions, hypotension, and pruritus [17]. A number of case reports and retrospective studies have also demonstrated similar positive safety results with intravenous and non-parenteral lacosamide [16,19,20,23]. All other investigations of the agent in SE to date have been positive, and no other cases of angioedema have been observed.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Other adverse events reported were angioedema, allergic skin reactions, hypotension, and pruritus [17]. A number of case reports and retrospective studies have also demonstrated similar positive safety results with intravenous and non-parenteral lacosamide [16,19,20,23]. All other investigations of the agent in SE to date have been positive, and no other cases of angioedema have been observed.…”
Section: Discussionmentioning
confidence: 49%
“…The agent has been demonstrated to exert its anticonvulsant effects through the enhancement of slow inactivation of voltagegated sodium channels [18]; however, the precise mechanism of action of the drug has yet to be fully confirmed. Lacosamide is available in both oral and intravenous formulations, and in its intravenous form has shown promise as a treatment for SE [16,19,20]; nevertheless, prospective data of the use of this agent in such patients are limited.…”
Section: Introductionmentioning
confidence: 97%
“…33 Phenytoin/fosphenytoin, valproic acid, levetiracetam, and phenobarbital can all be considered as potential adjunct second-line therapies. Intravenous lacosamide [34][35][36] and oral topiramate [37][38][39] have also been suggested for refractory SE.…”
Section: Treatment Of Focal Motor Status Epilepticus and Nonconvulsivmentioning
confidence: 99%
“…Использование ЛКСМ при ЭС в качестве первого или второго АЭП привело к купирова-нию статуса в 100% случаев, в качестве третьего -в 81%, а в качестве четвертого и на более позднем этапе -в 75%! ЛКСМ оказался эффективным при бессудорожном [8,9] и рефрактерном бессудорожном ЭС [10]. Отмечена высокая эффективность ЛКСМ при хорошей переносимости (всего 2 случая зуда и сыпи из 48 наблюдений).…”
Section: о б з о рunclassified